The Correlation of Age, Gender, Heredity, Smoking Habit, Obesity, and Salt Consumption with Hypertension Grade in Cirebon, Indonesia - Hamzah, Alif; Khasanah, Uswatun; Norviatin, Dini (GHMJ (Global Health Management Journal), 2019)
Background: Hypertension is one of the most global killer diseases that causes death. The World Health Or- ganiza on es mated around 1.5 billion people in the world will be diagnosed with hypertension every year. The increasing incidences of hypertension in the world may be affected by several predictors including age, sex-linked, heredity, smoking habit, obesity, and salt consump on. This study has objec ve to examine those predictors to hypertension grade. Methods: This research was used observa onal analy c method with cross-sec onal study. This study involved 136 respondents who came to Kalijaga Permai Public Health Center, Cirebon City. The variables were measured by microtoise, sphygmomanometer, stethoscope, scales, and ques onnaires. Spearman correla on test and lo- gis c regression test was analyzed for this study. Results: 59.9% of respondents were in hypertension grade 1 and 54% of respondents were in high risk age. The bivariate results revealed that age, sex-linked, heredity, and salt consump on were sta s cally correlated with hypertension grade (p=0.001). However, smoking habit and obesity were not sta s cally correlated. Mul vari- ate analysis found that those who add extra salt were 3.3 mes more likely to have hypertension grade 2 and those in high risk age were 3.1 more likely to have hypertension grade 2 as well. Compared with female and those who have nega ve heredity, male and posi ve heredity were 2.7 mes more likely to have hypertension grade 2. Conclusion: Salt consump on, age, sex-linked, heredity was significantly correlated with hypertension grade. Salt consump on was a risk factors which has the highest impact. Public health center should educate people about the recommenda on of daily salt intake to prevent the excessive intake that may affect hypertension.